Treatment outcomes of patients with tracheobronchial mucoepidermoid carcinoma compared with those with adenoid cystic carcinoma. Issue 10 (October 2020) - Wang, Yalong; Cai, Songhua; Xue, Qi; Mu, Juwei; Gao, Yushun; Tan, Fengwei; Mao, Yousheng; Wang, Dali; Zhao, Jun; Gao, Shugeng; He, Jie
Abstract: Objective: Tracheobronchial mucoepidermoid carcinoma (TMEC) is an extremely rare salivary gland-type neoplasm. We aimed to explore the clinical characteristics and prognosis of TMEC and to compare them with those of another rare salivary gland-type neoplasm, tracheobronchial adenoid cystic carcinoma (TACC). Method: We performed a retrospective review of all patients pathologically diagnosed with TMEC between 1965 and 2017 at our institution. We reviewed the patients' clinical characteristics, treatment methods and outcomes and compared the results of TMEC and TACC patients. Results: A total of 115 consecutive patients, including 107 who underwent surgery and 8 who received nonoperative therapy, were included in our study. The 1-, 2-, and 5-year survival rates were 97.89%, 94.17%, and 90.50%, respectively, in the surgical group and 83.33%, 41.67% and 0.00%, respectively, in the nonoperative group. The multivariate analysis showed that N stage was an independent prognostic factor for overall survival (OS). TMEC patients were younger, had a shorter complaint duration, had fewer symptoms, had more bronchial tumors, and were more likely to undergo surgical treatment and achieve an R0 resection (surgically treated patients) than TACC patients; furthermore, TMEC patients had a significantly better OS than TACC patients ( P  < 0.050). Conclusions: TMEC has different characteristics and a better prognosis than TACC, which may reflect the different biological behaviors of these two salivary gland neoplasms. Radical treatment and close follow-up are critical for surgically treated TMEC patients with lymph node metastasis.